O emprego na economia do Brasil entre 2014/2020: uma análise através do método estrutural-diferencial e dos desastres naturais - Pavin, Eduardo Damiani (2022)
This study sought to assess whether the impact that employment, analyzed using the structural-differential method, can have on understanding the effects of crises on the Brazilian economy. To this end, data from the website of the General Registry of Employed and Unemployed Persons of the Ministry of Labor and Social Security were used as a data collection instrument. The analysis was carried out using the structural-differential method, thus investigating the behavior of the 5 major Brazilian regions in relation to employment data and their relationship with the impacts caused by natural disasters. The calculated values ​​were extracted based on the 5 economic sectors of the country - industry, construction, agriculture, commerce and services. The results demonstrated that in all areas, there were significant impacts on the labor market during the periods of the crises analyzed. The COVID-19 pandemic caused significant impacts in all economic sectors from the perspective of employment. This study contributes to the advancement of studies on the labor market and the impact of economic crises in this context, as well as identifying the volatility of Brazilian scenarios during periods of crisis, thus generating intense changes in the maintenance of employment and contributing to uncertainties regarding the national economy.